Population structure and genetic diversity in Eucalyptus pellita based on SNP markers - Wang, Chubiao; Lan, Jun; Wang, Jianzhong; He, Wenliang; Lu, Wanhong; Lin, Yan; Luo, Jianzhong (Frontiers in Plant Science, 2023)
Eucalyptus pellita has the characteristics of rapid growth and high resistance. However, there is little research on molecular breeding of E. pellita, which is essential to shortening breeding life and selecting quality varieties. Therefore, a crucial step before selective breeding can be carried out to increase the wood quality of E. pellita is identifying genetic diversity and population structure using single nucleotide polymorphism (SNP) markers. In this study, the genetic diversity of 1st generation 196 E. pellita families from 23 geographically defined was assessed using 1,677,732 SNP markers identified by whole genome resequencing. SNP annotation showed that the ratio of non-synonymous to synonymous coding mutations was 0.83. Principal component analysis (PCA), phylogenetic tree, and population structure analysis permitted the families to be categorized into three groups, one of which (G2) contains most of the Indonesian (IDN) and Papua New Guinea (PNG) families. Genetic relationship analysis showed that IDN was closely related to PNG. Genetic diversity analysis showed that He, PIC, I, and H mean values were 0.2502, 0.2027, 0.3815, and 0.2680, respectively. PCA analysis classified various provenances in QLD into two categories (G1 and G3). The genetic diversity of G3 was higher than that of G2. The results of genetic differentiation (Fst) showed that PNG region was divided into two groups (PNG1 and PNG2), the Fst (0.172) between QLD and PNG2 region was higher than QLD and PNG1, and the Fst (0.024) between IDN and PNG1 is smaller than IDN and PNG2. A Mantel test revealed a positive correlation between the genetic and geographic distance of E. pellita. This study has a certain reference value for genetic identification, germplasm preservation, and breeding of E. pellita. Also, it provides a basis for subsequent association analysis to explore excellent alleles and introduction.